Contribution of Building Materials to Urban Growth in Dodoma Tanzania`` - Babune, George Julius (International Journal of Scientific Research in Biological Sciences, 2023)
The Environmental Protection Plan (EPP) for the Prospecting and extraction of building materials had provided details of impacts. The issues of environmental concerns had also been identified including mitigation measures. The area for extract of building materials occupies about 49 acres. The planned activities will involve extraction and transportation of building materials to the markets in the Dodoma City. The positive impacts will include: employment creation, promotion of rural livelihoods, contribution to local trade, promotion of industrial development, and promotion of rural urban linkages. The negative impacts will involve: land degradation, Human Immune Virus (HIV) or Acquired Immune Deficiency Syndrome (AIDS) infection, accidents, water pollution, sound and noise pollution, deforestation, loss habitats for wild animals and solid waste generation and damage to roads. The mitigation and enhancement measures had been proposed including: conduct training of farmers, workers of safety and conservation, maintain ecological habitat for flora and fauna survival, good practices in production and waste treatment, and issues related to HIV/ AIDS education and prevention. The project will be continuously monitored through the reporting format with parameters already identified. The study recommended establishing the environmental management practices and undertaking training of the workers involved in the subsector and local community to familiarize with the impacts and management practices for environmental protection.